Analysing industrial manufacturing in-plant and in-service performance of asphalt mixtures cleaner technologies. (10th May 2016) - Sol-Sánchez, M.; Moreno-Navarro, F.; García-Travé, G.; Rubio-Gámez, M.C.
Abstract: Roads play a significant role in the development of societies. Considerable quantities of asphalt mixes are employed in their construction, with hot asphalt mix (HMA) technology being one of the most commonly used worldwide. In recent times, the development of sustainable technologies has become a priority for most governments, and to this end, warm mix asphalt (WMA) can be considered as a cleaner technology that allows for the production of asphalt mixtures under lower manufacturing temperatures. This in turn allows for a reduction in atmospheric emissions and fuel consumption in comparison with HMA. However, due to the novelty of WMA and the length of time required for the analysis of its performance in real roads, information regarding the feasibility of its use is not easy to obtain. This research therefore analyses the potential for manufacturing a WMA using the same discontinuous industrial plant and the spreading and compaction machinery available for a HMA mixture, whilst also including the construction of a trial section that allows for the study of the performance of the WMA during its service life in a real road. The results suggest that WMA can be produced without modifying the industrial manufacturing process, providing asphalt pavements with comparable (or even better) mechanical performance to that recorded when equivalent hot asphalt mixtures are used. These findings are encouraging for the potential use of this cleaner technology in road construction projects. Highlights: Warm mix asphalt (WMA) as a cleaner asphalt mixture technology to substitute hot mix asphalt (HMA). Viability of obtaining a WMA in a HMA conventional plant; without modifications. The WMA obtained reduces manufacturing costs and maintenance tasks being a cleaner technology. The WMA tested in a real road performed satisfactory. The WMA tested proved to be an environmentally option to conventional HMA.